Eficácia de três protótipos de um dispositivo para redução da dispersão de aerossol em atendimentos odontológicos em tempos de pandemia de covid-19 : um estudo de simulação realística e um ensaio clinico randomizado controlado - Baldasso, Camila Nehme (2022)
Introduction: Health services were heavily impacted by the COVID-19 pandemic, a disease caused by the SARS-CoV-2 virus. In dentistry, in addition to the usual personal protective equipment (PPE), it was necessary to adopt additional biosafety protocols, especially in view of the risk of cross-infection resulting from the production of aerosols during dental practice. In this scenario, in this dissertation, different prototypes of a device were developed and tested in order to reduce the dispersion of microparticles during dental procedures. This dissertation contains two studies: 1- a realistic simulation study that aimed to describe one of the device prototypes, evaluating its ability to reduce aerosol dispersion in simulated clinical care; and 2- a randomized controlled clinical trial whose objective was to analyze the microbiological efficacy and the ergonomic impacts of three prototypes of a device to reduce aerosol dispersion in dental care in times of a COVID-19 pandemic, testing the hypothesis that the use of the devices reduces the dispersion of particles by spraying compared to the standard control treatment. Methodology: In study 1, a prototype consisting of a rigid transparent acrylic structure, involving the patient's head, neck and chest, was fitted to the dental chair. This acrylic chamber was coupled to an aspiration system with negative pressure, for aspiration and filtering of the air inside the chamber. A simulated dental procedure was performed on a dummy, using a high-speed pen and a fluorescent dye in the water of the equipment. The simulation took place with or without the use of the device. The presence of dye was analyzed in several locations, such as operator's PPE, dental chair and operating room. In study 2, three prototypes were included, the acrylic structure with aspiration, only the acrylic structure and a structure made with rigid polyvinyl chloride (PVC) tubes surrounded by layers of translucent flexible PVC films. The three structures were used during dental care and the patients were randomly allocated, until reaching 15 individuals per group. The prototypes were evaluated from a microbiological and ergonomic analysis. Results: In study 1, in the simulation without the use of the device, the dye was identified in the following places: surgical gloves, operator's apron (waist, chest, legs, wrists), face shield, in the dental chair (backrest, reflector) and in the operating room floor. In the simulated procedure using the device, the dye was observed only on the surgical gloves and on the operator's apron cuff, in addition to the internal walls of the acrylic chamber and the suction system pipes. There was some limitation of movements and visualization by the operator with the use of the device. In study 2, the results of the ergonomic analysis revealed good acceptance by the patients during the use of the prototypes. On a scale of 1 to 5, with 1 being very bad and 5 being very good, the mean in the group that used the acrylic structure with suction was 4.07 ± (0.59), in the group with only the acrylic structure was 4.00 ± (0.88 ) and in the group with the PVC structure was 3.87 ± (0.64). Regarding the evaluation of the use of the device by dentists, it was possible to verify a significant increase in the feeling of security and protection, but with a significant impact on ergonomics. The microbiological analyzes showed that the use of the different prototypes of the device significantly reduced the contamination in the reflector (p=0.028) in relation to the control group (CG), as well as reduced the contamination that reaches the dental surgeon's PPE, such as in the apron (p=0.044) and in the face shield (p=0.017). Conclusions: Based on the findings of studies 1 and 2, it is possible to conclude that: a) the tested device represents a low-cost complementary resource for use in conjunction with standard PPE, and was able to reduce aerosol dispersion during practice simulated dentistry, especially in regions such as the operator's face shield and apron, the dental reflector and the operating room floor; b) the different prototypes of the tested device significantly reduced the microbial contamination generated during dental care, especially at points of the dental equipment, and the contamination that affects the dentist's PPE (face shield and apron) during clinical use; c) the use of different prototypes of the device did not change the average time of dental appointments; d) from the patients' perspective, the ergonomic impact of using the device was positive, with good general acceptance, with no differences between the different prototypes; e) from the perspective of dentists, the use of different prototypes of the device resulted in a significant increase in the feeling of safety and protection, but significantly reduced ergonomics in areas such as clinical visualization, physical access to the patient, ease of performing the procedure, agility movement and workspace. Finally, we point out that ergonomic improvements of the device are underway, and the present initiative may represent an actional biosafety resource in dentistry to face not only the current COVID-19 pandemic, but also to combat other infectious diseases and future epidemics.